2011
DOI: 10.1667/rr1281.1
|View full text |Cite
|
Sign up to set email alerts
|

l-Arginine is a Radioprotector for Hematopoietic Progenitor Cells

Abstract: l-Arginine is shown to protect hematopoietic progenitor (32D cl 3) cells from death due to exposure to γ radiation (137Cs). Some of the other intermediates in the urea cycle, namely ornithine and citrulline, plus urea itself, were not found to have any significant impact on cell survival after irradiation. Intriguingly, supplementation of irradiated cells with l-arginine results in decreased production of peroxynitrite, suggesting that suppression of superoxide generation by nitric oxide synthase in one or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Ferulic acid improves hematopoietic cell recovery in whole-body gamma irradiated mice 28 . L-arginine improves radioprotection for hematopoietic progenitor cells 29 . CpG-oligodeoxynucleotide, a synthetic analog of bacterial DNA, minimizes the bone marrow damage induced by total body irradiation 30 .…”
Section: Dicussionmentioning
confidence: 99%
“…Ferulic acid improves hematopoietic cell recovery in whole-body gamma irradiated mice 28 . L-arginine improves radioprotection for hematopoietic progenitor cells 29 . CpG-oligodeoxynucleotide, a synthetic analog of bacterial DNA, minimizes the bone marrow damage induced by total body irradiation 30 .…”
Section: Dicussionmentioning
confidence: 99%
“…Some mechanism has been proved to be radiation-resistant in other organisms. For example, arginine could protect hematopoietic progenitor cells against ionizing radiation in mammalian [21]. The existences of nodes involve different mechanisms (Table S1) suggest that different mechanisms may act in concert under the radiation stress.…”
Section: Discussionmentioning
confidence: 99%
“…L-arginine can increase the expansion of small intestinal stem cells (ISCS) by targeting rapamycin complex1 and inhibiting Wnt2B secretion in small intestinal (SI) organoid models. In addition, L-arginine therapy can protect the intestinal tract from injury ( Pearce et al, 2012 ). Zhang et al found that exogenous L-arginine could promote the proliferation and intestinal epithelial renewal of ISCS, and protect the gut from the injury induced by TNF-α and 5-FU in mice ( Hou et al, 2020 ).…”
Section: Arginine Metabolism and Stem Cellsmentioning
confidence: 99%